The principle of the 3Rs between aspiration and reality - Vitale, Augusto; Ricceri, Laura (Frontiers in Physiology, 2022)
The Principle of the 3Rs is widely recognised as the methodological and ethical backbone of contemporary animal research. Different authors also stress the reciprocal links among the 3Rs, and how these often complement and reinforce each other. We very much agree with this point, but in this contribution we would like to raise some problems related to the application of the “3Rs”. There is an obvious link among “Replacement, “Reduction” and “Refinement”, but it is worth to notice also that each “R” has its own conceptual characteristics, as well as its own level of applicability. For example, a realistic “methodological inertia” has to be expected more in the case of “Replacement” than in the case of “Refinement”. This also leads to a second order of issues, and here we will offer our experience as projects evaluators. The “3Rs” differ also in the possibility to verify how are applied by the proponents of research protocols involving the use of animal models. Sometimes it appears that the application of the Principle still resolves itself in the use of formulaic sentences, from which it is difficult to really understand the reality of the laboratory decisional and procedural processes. However, the demanding characteristics of the “3Rs” can vary greatly, and this is something that has to be considered. We propose that a network, or a virtual platform, of evaluators could help both researchers and evaluators for a more satisfactory understanding and pragmatic application of the Principle of the 3Rs.